Statistical Analysis of the Phase Velocity Distribution of Mesospheric and Ionospheric Waves Observed in Airglow Images Over a 16‐Year Period: Comparison Between Rikubetsu and Shigaraki, Japan. Issue 8 (23rd August 2018) - Tsuchiya, Satoshi; Shiokawa, Kazuo; Fujinami, Hatsuki; Otsuka, Yuichi; Nakamura, Takuji; Yamamoto, Mamoru
Abstract: Atmospheric gravity waves (AGWs) in the mesopause region and medium‐scale traveling ionospheric disturbances (MSTIDs) in the thermosphere from 1999 through 2014 were studied by applying a three‐dimensional spectral analysis technique to airglow images at wavelengths of 557.7 (emission altitudes: 90–100 km) and 630.0 nm (emission altitudes: 200–300 km) obtained at Rikubetsu (43.5°N, 143.8°E) and Shigaraki (34.8°N, 136.1°E), Japan. To our knowledge, such a long‐term multipoint analysis of AGWs and MSTIDs using airglow images has not been reported previously. The propagation direction of mesospheric AGWs seen in 557.7‐nm airglow images at both stations was northeastward in summer and southwestward in winter, probably due to wind filtering of these waves by the mesospheric jet. In winter, the propagation direction of AGWs shifted from southwestward to northwestward as time progressed from evening to morning at both stations, which can also be explained by the wind filtering effect. The propagation direction of AGWs changed from southwestward to northeastward at Rikubetsu during a zonal wind reversal at 60°N at 10 hPa, caused by stratospheric sudden warming (SSW). No such a SSW‐associated change was identified at Shigaraki, indicating that the effect of SSW wind reversal reached only the Rikubetsu latitudes. For MSTIDs, the major propagation direction was southwestward with a minor northeastward peak for all seasons at both stations. A negative correlation was found between the yearly variation in power spectral density and solar F10.7 flux. This negative correlation can be explained by considering the linear growth rate of the Perkins instability. Key Points: Long‐term analysis of the horizontal velocity of waves was made for airglow images at two different latitudes Seasonal variation in the atmospheric gravity wave propagation direction was analyzed at both observation stations Negative correlation was found between medium‐scale traveling ionospheric disturbances and solar activity